CT-GUIDED PERCUTANEOUS TRANSTHORACIC FINENEEDLE ASPIRATION BIOPSY OF SMALL PERIPHERAL PULMONARY LESIONS - Zhang, Jun; Zhao, Huiru; Fu, Zhimin; Qu, Hengchun; He, Anguang; Li, Houwen (Chinese Journal of Cancer Research, 2013)
CT-guided percutaneous transthoracic fine needle aspiration biopsy (PTFNAB) was performed in twenty. four sputum-negative cases of small peripheral pulmonary lesions smaller than 2 cm in diameter, which are not easily diagnosed or accessible to fibrobronchoscopes. After thin-slide scanning and localization with Somatom DR-H computed tomography, pulmonary nodules were biopsied with a 20 Gauge needle guided by a ruler specially designed. Biopsy materials were used for cyto-and histopathologic examinations. The diagnosis accuracy of biopsy was evaluated by the result of postoperative pathology and/or follow-up for 2 years. Sixteen pulmonary lesions were proved to be malignant and 8 were benign. The sensitivity was 75.0% (12/16), speciti-vity 100% (8/8) and accuracy 83.3% (20/24) according to cytopathology and 87.5% (14/16), 100% (8/8), 91.7% (22/24) by histopathology, respectively. Two cases of early.stage peripheral lung cancer were detected and proved by operation. CT-guided PTFNAB is safe and quick for diagnosis with high accuracy for small peripheral pulmonary lesions which are usually negative in sputum examination and bronchoscopy. PTFNAB should be routinely used in the diagnosis of lung neoplasms.